Historical background and conceptual framework of the FAO model code of forest harvesting practice - Dykstra, D.P. (1997)
The FAO Model Code of Forest Harvesting Practice was published in early 1995 by the Food and Agriculture Organization of the United Nations as a model which can be used by FAO member countries contemplating the development of their own codes of forest practice. This paper outlines the purposes of the FAO Model Code, reviews the historical events leading to its preparation, and summarises the philosophical foundation upon which it has been constructed.